On the utilization controversy: A theoretical and empirical discussion of the Kaleckian model of growth and distribution - Michalis Nikiforos (Levy Economics Institute of Bard College, 2012)
This paper examines the utilization controversy around the Kaleckian model of growth and distribution. We show that the Federal Reserve data on capacity utilization, which have been used by both sides of this debate, are the wrong kind of data for the issue under examination. Instead, a more appropriate measurement can be derived from the data on the Average Workweek of Capital. We argue that the long-run dynamic adjustment proposed by Kaleckian scholars lacks a coherent economic rationale, and provide an alternative path toward the endogeneity of the desired utilization at the micro and macro levels. Finally, we examine the proposed adjustment mechanism econometrically. Our results verify the endogeneity of the normal utilization rate.
Keywords: B50; E12; E22; 330; Kaleckian; long run; economies of scale; utilization